2021
DOI: 10.3390/su13084227
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of High-Speed Rail on Regional Accessibility and Spatial Development—Updated Evidence from China’s Mid-Yangtze River City-Cluster Region

Abstract: There has been long and ongoing interest in the impacts of high-speed rail (HSR) on regional spatial development. Most existing studies, however, reported findings at relatively coarse geographic scales, i.e., at the prefecture-city or above level in the Chinese context. This paper presents the empirical evidence of HSR impacts from the county-level cities in China’s Mid-Yangtze River City-Cluster Region (MYRCCR). The study utilized rail time data and the socio-economic data for MYRCCR’s 185 county-level citie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…These studies fall into three classifications: (i) those focusing on the structure of the railway transport network [25,26]; this type of research aims to analyze how the characteristics of the railway network change during its upgrade, and the frequently used indices includes the alpha index, gamma index, beta index, and the diameter of the network; (ii) studies focusing on how railway upgrading impacts the accessibility or connectivity of cities or regions; HSR can improve accessibility to the areas along the line, but its degree of influence varies with the location, scale, and basis of development of a given region or city [27][28][29]; (iii) the third line of research focuses on how HSR impacts regional economic development [30,31]; however, there is still no consensus. Among those studies, some hold that HSR promotes an increase in population, employment, gross domestic product (GDP) and local budgets [32][33][34] and has a positive effect on the coordinated development of the regional economy [35][36][37], but some hold the opposite or neutral view [38][39][40]. The impact of HSR on the economic disparity is also controversial.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These studies fall into three classifications: (i) those focusing on the structure of the railway transport network [25,26]; this type of research aims to analyze how the characteristics of the railway network change during its upgrade, and the frequently used indices includes the alpha index, gamma index, beta index, and the diameter of the network; (ii) studies focusing on how railway upgrading impacts the accessibility or connectivity of cities or regions; HSR can improve accessibility to the areas along the line, but its degree of influence varies with the location, scale, and basis of development of a given region or city [27][28][29]; (iii) the third line of research focuses on how HSR impacts regional economic development [30,31]; however, there is still no consensus. Among those studies, some hold that HSR promotes an increase in population, employment, gross domestic product (GDP) and local budgets [32][33][34] and has a positive effect on the coordinated development of the regional economy [35][36][37], but some hold the opposite or neutral view [38][39][40]. The impact of HSR on the economic disparity is also controversial.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The construction of high-speed railways improves overall regional accessibility and it significantly benefits areas that are situated along the route; however, it also increases regional imbalances [18]. In terms of urban agglomerations, high-speed railways can effectively promote the regional integration of urban clusters [19][20][21]. There are many ways to measure accessibility, such as grid accessibility [22], weighted average travel time [23,24], the cumulative opportunity measure [25], and the gravity model [26,27].…”
Section: Accessibilitymentioning
confidence: 99%
“…As an essential part of transportation infrastructure [1], the HSR plays an instrumental role in global economic, social, and environmental development [2][3][4], as well as the changes in the regional development pattern [5,6]. Ahlfeldt and Feddersen empirically found that the HSR connecting Cologne and Frankfurt (Germany) increased the GDP of the passing county by 8.5% [7].…”
Section: Introductionmentioning
confidence: 99%